From Classical Pedagogy to Education 4.0: Continuity of Methodology, Approaches and Principles (Journal of Educational Sciences, 2022)
The article actualizes the need for a theoretical substantiation of the theory of learning and personalitydevelopment at the stage of early, middle and late adulthood. The implicit theory of intelligence, synergetic and eutagogical approaches are considered; knowledge management approaches for the knowledgesociety (phenomena of explicit and implicit knowledge, knowledge flows, diffusion of knowledge andculture); ideas of peeragogy as Education 4.0. The continuity of “classical pedagogy → andragogy → heutagogy → peeragogy” is studied. The results of a survey of 1st year students about their implicit presentation of the doctrine are given. The survey involved 86 students of the Kazakh National University namedafter al-Farabi. It was found that 66.7% of students chose the understanding “learning is the acquisition offacts, methods, etc., which can be stored and applied in practice”, 25% – “learning is the accumulation ofknowledge” and 4.8% “learning is it is the interpretation and understanding of reality”, and 3.6% “teachingis the understanding of meaning and determination of meaning”. The attitude of students to the principlesof eutagogy and pyragogy has been studied. Most students approve of the principles of self-education.Key words: heutagogy, andragogy, synergetics, implicit theories of intelligence, personality development, self-education, knowledge management.